Retinoic acid-dependent transactivation of major histocompatibility complex class I promoters by the nuclear hormone receptor H-2RIIBP in undifferentiated embryonal carcinoma cells. - Nagata, T (1992)
H-2RIIBP is a member of the nuclear hormone receptor superfamily that binds to the region II enhancer of major histocompatibility complex (MHC) class I genes. The binding occurs through the GG(T/A)CA motif present also in many other genes. The role of H-2RIIBP in developmental regulation of MHC class I genes has been studied in undifferentiated N-Tera2 embryonal carcinoma cells by transient cotransfection of an expressible H-2RIIBP plasmid and a chloramphenicol acetyltransferase reporter gene linked to the MHC class I promoter. Transfection of the expression plasmid led to production of H-2RIIBP transcripts and enhanced MHC class I promoter activity in cells that were treated with retinoic acid but not yet differentiated. Retinoic acid concentrations required for transactivation overlapped with those capable of inducing morphological differentiation and expression of endogenous MHC class I genes in these cells. This enhancement was mediated by region II, as a heterologous thymidine kinase promoter driven by region II also served as a target for H-2RIIBP transactivation. Deletion of the bulk of the DNA-binding domain or the ligand-binding domain of H-2RIIBP, but not of the N-terminal domain, abolished transactivation, indicating that the former two domains are critical for the enhancement. Moreover, H-2RIIBP transactivation exhibited a strict cell-type restriction. As observed in other cell lines, N-Tera2 cells that had undergone differentiation failed to elicit transactivation, suggesting that H-2RIIBP acts in concert with a cofactor expressed in undifferentiated N-Tera2 cells that requires retinoic acid for its function. These results suggest that H-2RIIBP can function as a developmentally specific transcription factor for MHC class I genes.